Backscattering and transmission Raman spectroscopy systems in the quantitative analysis concentration of acetone solutions - T P Charoenrit; S Wicharn; C Puttharugsa; P Limnonthakul; W Sassuvun; P Buranasiri; S Plaipichit (My University, 2023)
Abstract Raman spectroscopy is a set of techniques based on Raman scattering properties, widely applied to analyze the composition of various substances. The techniques consist of 1) backscattering, which collects Raman signals scattered from the surface of a sample; and 2) transmission, which collects Raman signals transmitted by the surface of a sample in the opposite direction of a light source (which triggers less fluorescence than backscattering). In this paper, we will measure the Raman spectrum of acetone solution by the transmission Raman spectroscopy and the backscattering Raman spectroscopy systems that we set up. Those accessories we use are a 532-nanometer diode laser with 100 milliwatt power as the light source, a focusing lens, an objective lens used for amplifying the Raman signals scattered from the sample, and a long-pass filter used to block light with a wavelength shorter than 532 nanometers. For the experimental samples, there are acetone solutions each prepared at 1M, 3M, 5M, 7M, 9M, 11M, and 13M. In the results of this experiment, we found that the intensity of Raman peaks for each Raman shift of acetone and the molar concentrations of acetone measured by both systems have a linear function in the backscattering Raman system and have a quadratic function in the transmissions Raman system because in backscattering system have noise by fluorescence effect more than in transmission system and it might be the effect of the Beer-Lambert law.
Keywords: Nanometre; Spectroscopy Techniques in Biomedical and Chemical Research